2012
DOI: 10.1029/2012gl052453
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal hydrological loading in southern Alaska observed by GPS and GRACE

Abstract: We compare vertical seasonal loading deformation observed by continuous GPS stations in southern Alaska and modeled vertical displacements due to seasonal hydrological loading inferred from GRACE. Seasonal displacements are significant, and GPS‐observed and GRACE‐modeled seasonal displacements are highly correlated. We define a measure called the WRMS Reduction Ratio to measure the fraction of the position variations at seasonal periods removed by correcting the GPS time series using a seasonal model based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 127 publications
(102 citation statements)
references
References 28 publications
(33 reference statements)
1
101
0
Order By: Relevance
“…Davis et al [10] found high correlation of annual hydrologic variations between GRACE- and GPS-derived vertical surface displacements from their respective residual height time series in the Amazon Basin. Consistent seasonal displacements between GPS and GRACE have been demonstrated in West Africa [11], the Nepal Himalayas [12] and southern Alaska [13]. Perhaps due to technical errors in GPS data processing, poorer agreement between GRACE and GPS has also been reported over Europe [14] and over Central America [15].…”
Section: Introductionmentioning
confidence: 92%
“…Davis et al [10] found high correlation of annual hydrologic variations between GRACE- and GPS-derived vertical surface displacements from their respective residual height time series in the Amazon Basin. Consistent seasonal displacements between GPS and GRACE have been demonstrated in West Africa [11], the Nepal Himalayas [12] and southern Alaska [13]. Perhaps due to technical errors in GPS data processing, poorer agreement between GRACE and GPS has also been reported over Europe [14] and over Central America [15].…”
Section: Introductionmentioning
confidence: 92%
“…Figure 7 is a conceptualization of this process. Several studies have shown that GRACE gravity observations can model the earth's annual displacement (Davis et al, 2004;van Dam et al, 2007;Tregoning et al, 2009;Tesmer et al, 2011;Fu et al, 2012aFu et al, , 2012bNahmani et al, 2012). But, for GRACE, a discrepancy exists when comparing with GPS solutions for groundwater induced surface motions.…”
Section: Comparison Of Annual Water Variationsmentioning
confidence: 95%
“…Later, Davis et al (2004) suggested that annual displacement over the Amazon River Basin measured by GPS and modeled by GRACE (Gravity Recovery and Climate Experiment) data show a high agreement that proved the feasibility of deriving crustal seasonal variations from GRACE. Recent studies have focused on the combination of GPS, GRACE and loading models to infer earth's annual deformation (Dong et al, 2006;van Dam et al, 2007;Tregoning et al, 2009;Tesmer et al, 2011;Fu et al, 2012aFu et al, , 2012bNahmani et al, 2012;Demir et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Long-wavelength deformation signals, such as those expected along a subduction zone for instance [e.g., Béjar-Pizarro et al, 2013], can trade off with inaccurate satellite orbits, oceanic tidal load signals [DiCaprio and Simons, 2008], hydrological load signals [Fu et al, 2012], and long-wavelength variations in atmospheric stratification. Therefore, orbital parameters, which mimic long-wavelength phase variations, are often estimated during the inversion for tectonic parameters (i.e., slip rate, slip distributions,…), introducing more variability in the inversion process.…”
Section: Estimating Long-wavelength Deformationsmentioning
confidence: 99%
“…As shown by DiCaprio and Simons [2008], oceanic tidal load signals can be modeled and removed, while models are currently being developed to predict the influence of seasonal hydrological load on continents [e.g., Fu et al, 2012]. As a consequence, by using external data, such as GPS [e.g., Tong et al, 2013, Béjar-Pizarro et al, 2013, to constrain the residual orbital errors, or as the quality of estimated orbits should drastically increase with the future SAR missions, our method will allow one to decipher between long-wavelength atmospheric signals and long-wavelength deformation signals.…”
Section: Estimating Long-wavelength Deformationsmentioning
confidence: 99%